2005
DOI: 10.1212/01.wnl.0000150904.28131.dd
|View full text |Cite
|
Sign up to set email alerts
|

A trial of metoclopramide vs sumatriptan for the emergency department treatment of migraines

Abstract: When compared at 2 and 24 hours, aggressive (20 mg dosed up to four times) IV metoclopramide and 6 mg of subcutaneous sumatriptan relieved migraine headache pain comparably. Some secondary endpoints suggest that metoclopramide may be the preferable therapy for migraines presenting to the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 28 publications
2
108
0
7
Order By: Relevance
“…Among these medications, in a recent trial Friedman has shown a comparable effect in the ED of two abortive treatments for migraine attack, such as metoclopramide and sumatriptan s.c., for reduction of pain intensity at both 2 and 24 h [14].…”
Section: Therapeutical Approachmentioning
confidence: 91%
“…Among these medications, in a recent trial Friedman has shown a comparable effect in the ED of two abortive treatments for migraine attack, such as metoclopramide and sumatriptan s.c., for reduction of pain intensity at both 2 and 24 h [14].…”
Section: Therapeutical Approachmentioning
confidence: 91%
“…Существует версия, что эти препараты улучшают резорбцию анальгетиков [26]. Метоклопрамид также обладает собственной средней анальгетической эффективностью при пероральном использовании и высокой эффективностью при внутривенном введении [26]. В табл.…”
Section: N¹ 3(81) 2016unclassified
“…En ocasiones, tan solo con hidratar adecuadamente al paciente la sintomatología mejora y diferentes ensayos clínicos han demostrado que la metoclopramida tiene efecto analgésico per se en el caso de la migraña [26][27][28] . Si el paciente tiene mucha ansiedad o importantes trastornos del sueño deberá valorarse el uso de benzodiacepinas, como el diazepam a dosis bajas (5-10 mg) que con frecuencia se administran de forma combinada con AINES por vía im (diclofenaco y diazepam 5 mg).…”
Section: Figura 3 A) Tc Cerebral Sin Contraste: Hemorragia Subaracnounclassified